(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper we study the class of algebras satisfying a polynomial identity of degree six that are principal train algebras of rank 3 or 4, for which we give the explicit form of the train equation. If the rank of A is n≥ 5 in general, we provide the form of the train equation in some cases.